The Japanese Yen as an International Currency - Tavlas, George (IMF Working Papers; Working Paper ;, 1991)
The role of the Japanese yen as an international currency is assessed. It is found that the determinants of international-currency use imply some increase for the yen's use in international finance; however, the implications for the yen's use in international trade are mixed. It is also shown that, despite Japan's emergence as the world's largest net creditor nation, Japan's capital outflows have not significantly facilitated the yen's internationalization. Data are presented showing that, although the yen's use as an international currency has increased, it is still rather modest. Wider use of the yen as a regional currency in Asia has occurred, though a 'yen-zone' does not appear to be emerging.